Analysis of genomic variation in lung adenocarcinoma patients revealed the critical role of PI3K complex - Deng,Zhao min; Liu,Lin; Qiu,Wen hai; Zhang,Yong qun; Zhong,Hong yan; Liao,Ping; Wu,Yun hong (PeerJ, 2017)
Background Molecularly targeted therapies improved survival status of some patients with lung adenocarcinoma, which accounts for 40% of all lung cancers, and in-depth study of gene alterations is important for the personalized treatment. Methods The legacy archive data of clinical information and genomic variations under the project TCGA Lung Adenocarcinoma were downloaded from the GDC Data Portal using R package TCGAbiolinks. The significantly aberrant copy number variants segments were figured out using GAIA. After annotation, the genes involving CNV were used to get enriched pathways. Recurrent amplifications and deletions were identified and visualized by OncoPrint. Genomic alterations in cancer, including CNV and mutations, were represented in Circos. Results The significantly aberrant CNV segments were found, and the genes involved were associated with the immune system. In an analysis of 517 mutation annotated files, we highlighted 63 highly recurrent mutated genes which were associated with lung cancer signaling. These genes involved in important pathways related to cancer progression. The intersections between the genes involving in the significantly aberrant CNV and the genes harboring recurrent somatic SNP were extracted. The PI3K protein family acted as critical roles in the lung adenocarcinoma, since the components of the PI3K protein family include PIK3C2B, PIK3CA, PIK3R1 and so forth were presented in the intersections. Conclusion We represented a comprehensive annotation of genomic alterations in lung adenocarcinoma and proposed that PI3K signaling proteins were critical for it.
Keywords: Lung adenocarcinoma; Genomic variation; CNV; Mutations; PI3K